Historical Aspects of the Formation of the Jury Trial in Russia - BUSHNAYA, Natalya Viktorovna; PERSHINA, Elena Anatolyevna; KABAKOVA, Oksana Vasilyevna; STANKEVICH, Galina Viktorovna; CHUNIKHA, Anzhelika Arslanovna (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The relevance of the scientific analysis of the formation of the jury trial is due to the processes of updating the legal system, which are extremely complex and contradictory in legal, political and social aspects. The reform of the judicial system affects the most important areas – economic, social, political, and legal ones. Therefore, it becomes necessary to comprehend the rich theoretical and practical historical experience of Russia. The complexity of the processes of transformation of Russian statehood makes certain demands – a judicial reform should be theoretically justified both in the context of the traditions of Russian legal doctrines, which will allow proposing new approaches to the study of a legal doctrine, and in the context of the general theory of law, the methodology of which will allow using doctrines of the past for modern research of state-legal phenomena. The authors pursued the goal of revealing the features of the genesis of the jury trial in the conditions of the judicial reform of the second half of the nineteenth century. Such cognition methods as historical, comparative-legal, system-structural, logical, formal-legal ones have been used to achieve this goal. During the study, the authors made a conclusion that the historical aspect of the formation and development of the jury trial in Russia created prerequisites for analyzing the ʼadvantagesʼ and ʼdisadvantagesʼ of this form of legal proceedings in modern conditions. The novelty of the stated area of research is that within its framework, the problems and trends of interaction of Russian juridical science and the reform process in the late nineteenth and early twentieth centuries have been analyzed, and this is of great practical and scientific importance. The article focuses on considering the accumulated rich historical experience in order to identify the facets of the interface of juridical science and practice, determine the extent of its influence on the government direction of reforms, the ability to put the achieved level of gained knowledge to good use and respond to the social order of the time. Modern jurisprudence plays the same role; therefore, it is necessary to identify the problems that Russian legal scholars faced in the nineteenth century in order to avoid them now and in future, which is the aim of this research project. Therefore, the article is a comprehensive analysis of the trends of interaction and interdependence of juridical science and the process of in-depth reforming of the Russian state in the second half of the nineteenth century by the example of the formation of the jury trial.